2020
DOI: 10.1002/adfm.202003380
|View full text |Cite
|
Sign up to set email alerts
|

Climbing Plant‐Inspired Micropatterned Devices for Reversible Attachment

Abstract: Climbing plants have evolved over millions of years and have adapted to unpredictable scenarios in unique ways. These crucial features make plants an outstanding biological model for scientists and engineers. Inspired by the ratchet‐like attachment mechanism of the hook‐climber Galium aparine, a novel micropatterned flexible mechanical interlocker is fabricated using a 3D direct laser lithography technique. The artificial hooks are designed based on a morphometric analysis of natural hooks. They are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 55 publications
(64 reference statements)
0
29
0
Order By: Relevance
“…New Phytologist 2020). The moving-by-growing abilities of climbing plants have become models for the development of low-mass and low-volume robots capable of anchoring themselves, negotiating voids and more generally climbing (Fiorello et al, 2020;Mazzolai et al, 2020). The vision of combining nature and technology has also been achieved through the development of dynamic nonequilibrium materials systems.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…New Phytologist 2020). The moving-by-growing abilities of climbing plants have become models for the development of low-mass and low-volume robots capable of anchoring themselves, negotiating voids and more generally climbing (Fiorello et al, 2020;Mazzolai et al, 2020). The vision of combining nature and technology has also been achieved through the development of dynamic nonequilibrium materials systems.…”
Section: Reviewmentioning
confidence: 99%
“…Cuticles are concept generators for the regulation of water permeability (Mulama et al ., 2019), structural colours (Moyroud et al ., 2017) and sticky or nonfriction surfaces (Bergmann et al ., 2020). The moving‐by‐growing abilities of climbing plants have become models for the development of low‐mass and low‐volume robots capable of anchoring themselves, negotiating voids and more generally climbing (Fiorello et al ., 2020; Mazzolai et al ., 2020). The vision of combining nature and technology has also been achieved through the development of dynamic nonequilibrium materials systems.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work found that the reversible adhesion can be realized by imitating ratchet-like attachment mechanism of climbing plants. [18] Recently, smart adhesives inspired by natural animals have been developed, such as the magnetically actuated elastic energy storage adhesives inspired by octopus suckers, [19] the gecko inspired wedged surface utilized for dry adhesion, [20] tree frog inspired hierarchical structure, and insect inspired fibrillar pads for enhanced wet adhesion [21,22] and mussel inspired tissue adhesive hydrogel for sensors. [23] Despite extensive studies on artificial adhesives, they often need to introduce nondegradable cross-linking agent along with complex and time-consuming manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, biomedical devices [6] and structural adhesives [7] must safely adhere to surfaces during their application, but they should be easy to remove for reuse. Moreover, a recent challenge in soft robotics is to create climbing robots with reversible adhesion skills [8].…”
Section: Introductionmentioning
confidence: 99%